2020
DOI: 10.1038/s41598-020-58401-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplemental plant oils reduce methanogenesis from anaerobic microbial fermentation in the rumen

Abstract: Ruminants contribute to the emissions of greenhouse gases, in particular methane, due to the microbial anaerobic fermentation of feed in the rumen. The rumen simulation technique was used to investigate the effects of the addition of different supplemental plant oils to a high concentrate diet on ruminal fermentation and microbial community composition. The control (CTR) diet was a high-concentrate total mixed ration with no supplemental oil. The other experimental diets were supplemented with olive (OLV), sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 73 publications
10
34
1
1
Order By: Relevance
“…Feeding sunflower oil can effectively reduce enteric methane emissions of dairy cows (Bayat et al, 2017). Similar effects of vegetable oils on reducing methane emissions have been reported under in vitro conditions (Vargas et al, 2020). Recent work carried out at the University of Yucatan, Mexico (Flores-Santiago, E. unpublished results), has shown that by feeding palm oil (6% of ration DM) to hair Pelibuey sheep housed in respiration chambers, which were fed a low-quality basal ration of tropical C4 grass (Brachiaria brizantha) hay, methane yield was reduced by~14%, compared to a control treatment without palm oil.…”
Section: Enteric Methane Production By Cattle Fed Tropical Grassessupporting
confidence: 64%
“…Feeding sunflower oil can effectively reduce enteric methane emissions of dairy cows (Bayat et al, 2017). Similar effects of vegetable oils on reducing methane emissions have been reported under in vitro conditions (Vargas et al, 2020). Recent work carried out at the University of Yucatan, Mexico (Flores-Santiago, E. unpublished results), has shown that by feeding palm oil (6% of ration DM) to hair Pelibuey sheep housed in respiration chambers, which were fed a low-quality basal ration of tropical C4 grass (Brachiaria brizantha) hay, methane yield was reduced by~14%, compared to a control treatment without palm oil.…”
Section: Enteric Methane Production By Cattle Fed Tropical Grassessupporting
confidence: 64%
“…In general, the lipid content of seaweeds is low, varying between 1% and 5% DM [ 7 ], but there are substantial differences between the species when studying the elution profiles using untargeted LC-MS. Hemp leaves and stems, on the other hand, have higher lipid contents, of 19.97% and 8%, respectively [ 39 ]. Studies with ruminants have shown that PUFAs in the diet can reduce methane emissions by acting as hydrogen sinks because biohydrogenation of PUFAs can compete with methanogenesis for metabolic H 2 [ 40 ]. To our knowledge, no studies investigating glycolipids and methane reduction have been undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Variable effects of vegetable oils and unsaturated FA on CH 4 emission might be associated with the double bond number per FA, type of oil (free oil or whole seed), and composition (roughage-to-concentrate ratio) of the rations (134). An in vitro study of Vargas et al (141) shows that supplementation of vegetable oil (sunflower and linseed) at 6% in high-concentrate TMR has the potential to reduce CH 4 emission (up to 21-28%), butyrate concentration, and A:P, while increasing propionate concentration. Recently, a meta-analysis showed that addition of nitrates and vegetable oils in cattle diet has the ability to reduce CH 4 emission up to 6-20% (118).…”
Section: Interaction Of Dietary Fat With Rumen Microbiomementioning
confidence: 99%